Predictive value of vascular endothelial growth factor polymorphisms for maintenance bevacizumab efficacy in metastatic colorectal cancer: an ancillary study of the PRODIGE 9 phase III trial. (December 2022) - de Rauglaudre, Bernadette; Sibertin-Blanc, Camille; Fabre, Aurélie; Le Malicot, Karine; Bennouna, Jaafar; Ghiringhelli, François; Taïeb, Julien; Boige, Valérie; Bouché, Olivier; Chatellier, Thierry; Faroux, Roger; François, Eric; et al.
Background: Several studies have reported the impact of single nucleotide polymorphisms (SNPs) in vascular endothelial growth factor ( VEGF ) pathway genes on the efficacy of bevacizumab in metastatic colorectal cancer (mCRC), but results are still inconsistent. The PRODIGE 9 phase III study compared bevacizumab maintenance versus observation alone after induction chemotherapy with FOLFIRI plus bevacizumab. Objective: We evaluated the impact of SNPs of VEGF-A, VEGF receptors ( VEGFR-1, VEGFR-2 ), and hypoxia inducible factor-1α ( HIF-1α ) on tumor control duration (TCD), overall survival (OS), progression-free survival (PFS), and duration of first chemotherapy free-intervals (CFI). Patients and methods: We included 314/491 patients from PRODIGE 9 with a DNA blood sample available. Nine SNPs were genotyped on germline DNA using real-time Polymerase Chain Reaction TaqMan TM (Thermo Fisher Scientific, Waltham, MA, USA 02451). Results: In the bevacizumab arm, patients with the VEGFR-1 rs9582036 CC genotype ( n  = 14) had significantly longer TCD [22.4 months (95% confidence interval (CI): 14.75-not reached)] than patients with the AA or CA genotype [14.4 months (95% CI: 11.7–17.1)] ( p  = 0.036), whereas there was no significant difference in the observation arm. In the bevacizumab arm, no significant difference was found between the CC, and AA or CA genotype for OS [28.2 (95% CI: 18.1–42.8) versus 22.5 (95% CI: 18.6–24.6) months, p  = 0.5], PFS [9.4 (95% CI: 7.2–11.3) versus 9.2 (95% CI: 8.71–10.1)], and duration of the first CFI [4.6 (95% CI: 1.6–13.3) versus 4.14 (95% CI: 0.5–29.0) months, p  = 0.3]. Conclusion: Among mCRC patients treated with bevacizumab maintenance, those with the VEGFR-1 rs9582036 CC genotype experienced longer TCD. The presence of this genotype may thus predict a benefit of bevacizumab maintenance in mCRC.